The effects of swimming, cell therapy, and laser therapy on the expression of dynamin-related protein 1, muscle-specific ring finger protein 1, and mitofusin 2 genes in the testes of azoospermic rats - Amir Shapoori; Habib Asgharpour; Parvin Farzanegi; Neda Aghaei Bahman Beglou (Medical Laboratory Journal)
Background: One of the causes of infertility is azoospermia. The present study aimed to investigate the effects of swimming exercise, cell therapy, and laser therapy on the expression of genes involved in mitochondrial dynamics in the testicular tissue of azoospermic rats. Methods: In this experimental study, 40 rats (6-8-weeks old) were randomly assigned to 8 groups: 1) Healthy control, 2) patient, 3) sham, 4) laser, 5) exercise, 6) cell, 7) cell + laser, and 8) cell + exercise. The azoospermia model was induced using busulfan at a dose of 40 mg. Stem cells were transplanted once into the vas deferens at a concentration of 1000000 cells per rat. One week after cell transplantation, laser therapy was applied in three repetitions throughout the study period, with an interval of once a week, and after wound healing, the rats swam for 30 minutes a day, 5 days a week, for 8 weeks. To investigate the expression of the studied genes, tissue analysis was performed by the real-time polymerase chain reaction (RT-PCR) technique. Results: Azoospermia significantly reduced the expression of mitofusin 2 (Mfn2) and significantly increased the expression of dynamin-related protein 1 (Drp1) and muscle-specific RING finger protein 1 (Murf1) in testicular tissue. The use of interventional methods increased the expression of Mfn2, and significantly reduced the expression of Murf1. Conclusion: Based on the findings, the best changes were observed in the exercise + laser group. Therefore, it can be said that in rats using the azoospermia model, the simultaneous use of regular exercise interventions and laser therapy is the most effective.